Informing investment priorities of the Climate Services Partnership - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Climate change causes a great deal of uncertainty for farmers, as weather patterns become more unpredictable and extreme. Climate services, such as climate information and advisories, can help farmers manage climate risks and better adapt to changing circumstances. The Climate Services Partnership (CSP), launched in 2011, is a collaborative platform focused on knowledge sharing and network building, with the goal of promoting climate resilience and improving the capabilities of climate services at a global scale. CSP aims to engage a diverse network of organizations, researchers and donors, to help climate science guide investment and inform decision-making relating to adaptation and development. CCAFS Theme 2 on Climate Risk Management is a core sponsoring partner of the CSP. In 2012, several CCAFS research and communication efforts contributed to the investment prioritization of the CSP and other key members, leading to an increased emphasis on targeting smallholder farmers.